Identifying the trauma footprint of acquired brain injury - Durham, Christine (Henry Stewart Talks, 2016)
Identifying the trauma footprint of acquired brain injury using educational principles, Tools to investigate the trauma foot print of ABI, ABI cage study, Recommendation to lessen the trauma footprint of ABI
Reviewed at 2022/04/12